(untitled) (Global Journal of Human-Social Science, 2013)
This paper analyzes the diversified set of forms of participation of civil society organizations within the environmental policy during the government of Luiz Inacio Lula da Silva between 2003 and 2008. It takes into account aspects of effectiveness of participation and the democratization of debates on environment. It is based in qualitative research, with documental sources and interviews. Conclusions show the existence of a highly organized civil society that makes use of multiple mechanisms of participation to reach most effectiveness. It suggests, also, that effectiveness as well as democratization are intimately linked to the existence of institutional warrants, without which it is very difficult to oppose to economic interests..